Reinventing Shoes: United Nude - Koolhaas, Rem D (Architectural design, 2017)
Based in Amsterdam, United Nude is a world leader in the design of technically advanced architectural footwear. After working separately with fashion designer Iris van Herpen and architect Zaha Hadid, the practice went on to collaborate with a number of pioneering architects and product designers worldwide for an exhibition at the 2015 Salone del Mobile in Milan. As a cofounder of the firm, Rem D Koolhaas recounts the journey so far, revealing the questions it raises and the capacities and limitations of 3D printing in this field.